DOI: 10.31274/rtd-180813-5133
|View full text |Cite
|
Sign up to set email alerts
|

From chatting to confidence: a case study of the impact of online chatting on international teaching assistants' willingness to communicate, confidence level and fluency in oral communication

Abstract: Research question 3: Does the language experience of the chat actually transfer from the written mode into spoken language? Research question 4: Does chatting improve learners' fluency in oral communication? Statistical methods CHAPTER 4. RESULTS AND DISCUSSION 63 Impact of chat on willingness to communicate (WTC) 63 Impact of chat on state commimicative self-confidence. 66 Impact of chat on state anxiety 70 Impact of chat on state self-perceived competence Transfer of language experience from written to spoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The study showed that there was a significant increase in the students' speaking proficiency for both of the experimental groups (voice and text chat). The results for the text chat group affirmed the results of previous studies that text chat improved speaking skills and that language transfer was possible from the written environment of the text chat to spoken language (Abrams, 2003; Beauvois, 1997; Compton, 2002; Fitze, 2006; Lai & Zhao, 2006; Payne & Ross, 2005). The speaking test results for the voice chat group are important in that they provide one of the few sets of data in the field on the use of synchronous oral communication in CMC and for their quantitative nature and the sample size.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The study showed that there was a significant increase in the students' speaking proficiency for both of the experimental groups (voice and text chat). The results for the text chat group affirmed the results of previous studies that text chat improved speaking skills and that language transfer was possible from the written environment of the text chat to spoken language (Abrams, 2003; Beauvois, 1997; Compton, 2002; Fitze, 2006; Lai & Zhao, 2006; Payne & Ross, 2005). The speaking test results for the voice chat group are important in that they provide one of the few sets of data in the field on the use of synchronous oral communication in CMC and for their quantitative nature and the sample size.…”
Section: Discussionsupporting
confidence: 86%
“…As pair/group work is also argued to lower students' anxiety levels (Young, 1991), text chat, especially when carried out in pairs or groups, is likely to help learners break the “vicious circle” of reluctance to speak and low speaking competence as described by Compton (2002, p. 25).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The third study that was focused on tasks investigated a text chat-based task as a means of increasing students' willingness to communicate through oral language in the classroom (Compton 2002). The construct of "willingness to communicate" (MacIntyre, Clément, Dörnyei, & Noels 1998) was developed from research on individual differences in SLA and is intended to account for the important observation that communicative competence alone does not mean that learners will be successful at using the target language.…”
Section: Text Chat As Rehearsalmentioning
confidence: 99%
“…First, an important aspect of Internet communication tasks in particular is what the topics are, how interesting they are, and how current. In Compton's (2002) research, one of the main conclusions was that the topics of the chat discussions needed to be considered more carefully because the ones chosen seemed to spark negative attitudes in some of the participants. In the research of Sauro (2001), for example, among the most important decisions to be made in developing the tasks was to decide from the enormous range of available materials, what should be used for the tasks.…”
Section: Topics and Actionsmentioning
confidence: 99%